2017
DOI: 10.18632/oncotarget.15467
|View full text |Cite
|
Sign up to set email alerts
|

Control of long-distance cell-to-cell communication and autophagosome transfer in squamous cell carcinoma via tunneling nanotubes

Abstract: Tunneling nanotubes (TnTs) are thin channels that temporally connect nearby cells allowing the cell-to-cell trafficking of biomolecules and organelles. The presence or absence of TnTs in human neoplasms and the mechanisms of TnT assembly remains largely unexplored. In this study, we have identified TnTs in tumor cells derived from squamous cell carcinomas (SCC) cultured under bi-dimensional and tri-dimensional conditions and also in human SCC tissues. Our study demonstrates that TnTs are not specific of epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 42 publications
2
71
1
Order By: Relevance
“…An interesting question relates to the specific composition of the intermediate filaments in TMTs, given the ~70 filament forming intermediate filament proteins found in mammals (Chung et al, 2013). Thus far, CK7 (Veranič et al, 2008;Resnik et al, 2018), CK19 (this study), and vimentin (Ady et al, 2014;Sáenz-de-Santa-María et al, 2017) have been identified in this context. In view of the growing appreciation for the pleiotropic roles of intermediate filament in cancer (Karantza, 2011), their function in TNTs and TMTs assumes greater importance.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…An interesting question relates to the specific composition of the intermediate filaments in TMTs, given the ~70 filament forming intermediate filament proteins found in mammals (Chung et al, 2013). Thus far, CK7 (Veranič et al, 2008;Resnik et al, 2018), CK19 (this study), and vimentin (Ady et al, 2014;Sáenz-de-Santa-María et al, 2017) have been identified in this context. In view of the growing appreciation for the pleiotropic roles of intermediate filament in cancer (Karantza, 2011), their function in TNTs and TMTs assumes greater importance.…”
Section: Discussionsupporting
confidence: 53%
“…Microtubules could play clear roles in organelle trafficking within TMTs, but also may be important in maintaining the wider diameter of TMTs (Zhang et al, 2019). A number of intermediate filament proteins have been identified in TNTs, including cytokeratins and vimentin (Veranič et al, 2008;Ady et al, 2014;Sáenz-de-Santa-María et al, 2017;Resnik et al, 2018). We find abundant CK19 in TMTs from pancreatic cancer cells both in culture and in a tumor environment.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Normal fibroblast-like primary cultures (NF) were derived from the oral mucosa of a non-cancerous young patient. All cell lines were grown as previously described [16] and were periodically tested for human pathogens and mycoplasma infection. To avoid cross-contamination and phenotype changes, the cell lines have not been maintained in long-term cultures.…”
Section: Cell Culturementioning
confidence: 99%